ANALISIS MEMORABLETOURISM EXPERIENCE PADA MASA COVID-19 DI OBJEK WISATA AIR DINGIN BATU GADANG PADANG - Raiyan Rasaki Syafrizal; Dwi Pratiwi Wulandari* (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
One of the purpouse of this research is to find out the analysis of the memorable tourism experience during the COVID-19 period in the tourism object of Air Dingin Batu Gadang Padang. The type of research is quantitative descriptive using a survey method. There are 5,120 populations in this study and a sample of 100 respondents. The sampling technique applied in this study used non-probability sampling in the form of purposive sampling. The results of this research show an analysis of the memorable tourism experience during the Covid-19 period. The results of this study indicate that the Analysis of the Memorable tourism Experience During the Covid-19 Period at the tourism object of Air Dingin Batu Gadang Padang overall is in the category of good enough, that is in 47%.Keywords: Memorable, Tourism Experience, Covid